ASPEK KLINIS DAN PENATALAKSANAAN MENINGITIS TUBERKULOSA - Kiking Ritarwan* (NEURONA, 2011)
INTRODUCTION TUBERCULOUS MENINGITIS TBM IS ONE OF THE EXTRAPULMONAL TUBERCULOUS IT IS SUBACUTELY CENTRAL NERVOUS SYSTEM INFECTION FROM LUNG PRIMARY FOCUS THE ROUTE OF THE BACTERIA TO THE MENINGEN USUALLY VIA HEMATOGEN SPREADING FROM RESPIRATORY TRACT TUBERCULOUS IS ACID FAST ORGANISM MYCOBACTERIUM TUBERCULOUS WHICH PROPAGATED THROUGH DROPLET NUCLEUS ON THE AIRWAY TUBERCULOUS MENINGITIS DIAGNOSIS BASED ON CLINICAL EXAMINATION CSF ANALYSIS LED MRICT SCAN VIEW AND HISTORY OF CONTACT TUBERCULOUS PERSON ANTI DRUG TUBERCULOSA TREATMENT CHEMOTHERAPY REGIMEN ARE THE BEST TREATMENT OF TBM PATIENTS